Effects of Lycium barbarum polysaccharides supplemented to high soybean meal diet on immunity and hepatic health of spotted sea bass Lateolabrax maculatus - Liu, Longhui; Zhao, Yanbo; Huang, Zhangfan; Long, Zhongying; Qin, Huihui; Lin, Hao; Zhou, Sishun; Kong, Lumin; Ma, Jianrong; Li, Zhongbao (Frontiers in Immunology, 2024)
High soybean meal diet (HSBMD) decreased the immunity and damaged the liver health of spotted sea bass; in this study, Lycium barbarum polysaccharides (LBP) was added to HSBMD to explore its effects on the immunity and liver health. The diet with 44% fish meal content was designed as a blank control. On this basis, soybean meal was used to replace 50% fish meal as HSBMD, and LBP was added in HSBMD in gradient (1.0, 1.5, 2.0 g/kg) as the experimental diet. 225-tailed spotted sea bass with initial body weight of 44.52 ± 0.24 g were randomly divided into 5 groups and fed the corresponding diet for 52 days, respectively. The results show that: after ingestion of HSBMD, the immunity of spotted sea bass decreased slightly and hepatic tissue was severely damaged. And the addition of LBP significantly improved the immune capacity and protected the hepatic health. Specifically, the activities of serum lysozyme (LZM), immunoglobulin M (IgM), liver acid phosphatase (ACP) and alkaline phosphatase (AKP) were increased, and serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities were significantly decreased, and hepatic morphology was improved. In the analysis of transcriptome results, it was found that toll-like receptor 3 (TLR3) and toll-like receptor 5 (TLR5) were down-regulated in toll-like receptor signaling pathway. And LBP may protect hepatic health by regulating Glycolysis/Gluconeogenesis, Insulin signaling pathway, Steroid biosynthesis and other glucolipid-related pathways. In conclusion, the addition of LBP in HSBMD can improve the immunity and protect the hepatic health of spotted sea bass, and its mechanism may be related to glucose and lipid metabolism.